The resistance phenomenon in microbes and infectious disease vectors : implications for human health and strategies for containment : workshop summary - Knobler, Stacey (Online access: NCBI NCBI Bookshelf., 2003)
And proceedings of a February 2002 workshop held in Washington, D.C. by the Forum on Emerging Infections to explore the causes and consequences of the resistance phenomenon. An opening summary and assessment chapter discusses the core messages emerging from the speakers' presentations and ensuing discussions. Twenty-four contributions are organized into sections on an introduction and overview of the resistance phenomenon, microbe resistance, vector resistance, the economics of resistance, factors contributing to the emergence of resistance, emerging tools and technologies for countering resistance, and strategies to contain the development and consequences of resistance. No subject index. Annotation : 2004 Book News, Inc., Portland, OR (booknews.com).